Respuesta :

Answer:

x = 3

y = -1

Step-by-step explanation:

x + y = 2 ---------------------(I)

x -y = 4

   x =  4 + y -----------------(II)

Substitute x = 4 + y in equation (I)

4 + y + y = 2

4 + 2y = 2

Subtract 4 from both sides

2y = 2 - 4

2y = - 2

Divide both sides by 2

y = -2/2

y= -1

Substitute y = -1 in equation(II)

x = 4 - 1

x = 3

We have following two given equations which are:

[tex]\implies\sf{x + y = 2 \: ...(1)}[/tex]

[tex]\implies\sf{x - y = 4}[/tex]

[tex]\implies\sf{x = 4 + y \: ...(2)}[/tex]

Now replacing the value of x of equation (2) in equation (1),

[tex]\implies\sf{x + y = 2}[/tex]

[tex]\implies\sf{4 + y + y = 2}[/tex]

[tex]\implies\sf{4 + 2y = 2}[/tex]

[tex]\implies\sf{2y = 2 - 4}[/tex]

[tex]\implies\sf{2y = - 2}[/tex]

[tex]\implies\sf{y = \frac{ - 2}{2} }[/tex]

[tex]\implies\sf{y = - 1}[/tex]

Now replacing y = -1 in equation (1),

[tex]\implies\sf{x + y = 2}[/tex]

[tex]\implies\sf{x + ( - 1) = 2}[/tex]

[tex]\implies\sf{x - 1 = 2}[/tex]

[tex]\implies\sf{x = 2 + 1}[/tex]

[tex]\implies\sf{x = 3}[/tex]

  • The values of x and y are 3 and -1